TLR4 and Caveolin‐1 in Monocytes Are Associated With Inflammatory Conditions in Diabetic Neuropathy. Issue 3 (16th December 2016) - Zhu, T; Meng, Q; Ji, J; Zhang, L; Lou, X
Abstract : The purpose of this study was to investigate the expression of TLR4 and caveolin‐1 in monocytes among healthy volunteers as well as those with type‐2 diabetes mellitus (T2DM) and diabetic peripheral neuropathy (DPN). Nineteen healthy control subjects, 18 patients with T2DM, and 20 patients with DPN were enrolled. Toll‐like receptor (TLR)4, caveolin‐1, MyD88, phosphorylated IκB, and plasma TNF‐α and interleukin (IL)‐6 were measured using real‐time polymerase chain reaction, Western blotting, and enzyme‐linked immunosorbent assay. Compared with the other two groups, the DPN group had higher expression of TLR4, MyD88, phosphorylated IκB, TNF‐α, and IL‐6, but significantly lower levels of caveolin‐1 and total IκB in monocytes. Plasma concentrations of TNF‐α and IL‐6 were positively correlated with TLR4 and negatively correlated with caveolin‐1 in patients with DPN. Plasma concentration of TLR4 was negatively correlated with caveolin‐1 in patients with DPN. Reduced expression of caveolin‐1 in monocytes could aggravate the TLR4‐mediated inflammatory cascade.